Spatial analysis of groundwater hydrochemistry through integrated multivariate analysis: a case study in the urbanized Langat Basin, Malaysia - Mohamad Zainol, Nur Fatihah; Zainuddin, Azim Haziq; Ley, Juen Looi; Aris, Ahmad Zaharin; Mohd Isa, Noorain; Sefie, Anuar; Ku Yusof, Ku Mohd Kalkausar (MDPI AG, 2021)
Rapid urbanization and industrial development in the Langat Basin has disturbed the groundwater quality. The populations’ reliance on groundwater sources may induce possible risks to human health such as cancer and endocrine dysfunction. This study aims to determine the groundwater quality of an urbanized basin through 24 studied hydrochemical parameters from 45 groundwater samples obtained from 15 different sampling stations by employing integrated multivariate analysis. The abundance of the major ions was in the following order: bicarbonate (HCO3−) > chloride (Cl−) > sodium (Na+) > sulphate (SO42−) > calcium (Ca2+) > potassium (K+) > magnesium (Mg2+). Heavy metal dominance was in the following order: Fe > Mn > Zn > As > Hg > Pb > Ni > Cu > Cd > Se > Sr. Classification of the groundwater facies indicated that the studied groundwater belongs to the Na-Cl with saline water type and Na-HCO3 with mix water type characteristics. The saline water type characteristics are derived from agricultural activities, while the mixed water types occur from water–rock interaction. Multivariate analysis performance suggests that industrial, agricultural, and weathering activities have contributed to groundwater contamination. The study will help in the understanding of the groundwater quality issue and serve as a reference for other basins with similar characteristics.